2016
DOI: 10.1002/eat.22598
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers and facilitators towards help‐seeking for eating disorders: A systematic review

Abstract: Programs targeting prevention and early intervention for eating disorders should focus on reducing stigma and shame, educating individuals about the severity of eating disorders, and increasing knowledge around help-seeking pathways for eating disorders. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2017; 50:9-21).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
313
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(344 citation statements)
references
References 70 publications
(260 reference statements)
24
313
4
3
Order By: Relevance
“…This qualitative finding is consistent with prior studies about barriers to ED treatment (Ali et al, 2017;Eisenberg, Nicklett, Roeder, & Kirz, 2011;Lipson et al, 2017). This qualitative finding is consistent with prior studies about barriers to ED treatment (Ali et al, 2017;Eisenberg, Nicklett, Roeder, & Kirz, 2011;Lipson et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This qualitative finding is consistent with prior studies about barriers to ED treatment (Ali et al, 2017;Eisenberg, Nicklett, Roeder, & Kirz, 2011;Lipson et al, 2017). This qualitative finding is consistent with prior studies about barriers to ED treatment (Ali et al, 2017;Eisenberg, Nicklett, Roeder, & Kirz, 2011;Lipson et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Although it is well known that EDs are characterized by social isolation (Ali et al, 2017;Fairburn & Harrison, 2003;Fisher et al, 1995;Ison & Kent, 2010;Kerr-Gaffney, Harrison, & Tchanturia, 2018;Treasure et al, 2010), our study explores this social stigma on a university campus. Participants largely perceived themselves as isolated from their peers, noting that eating communally and drinking alcohol in social environments were alienating.…”
Section: Discussionmentioning
confidence: 99%
“…Several other specific barriers impede seeking and obtaining mental health services generally and specific to eating disorders (Ali et al, ; Andrade et al, ; Corrigan et al, ; Hinshaw & Stier, ). Although their elaboration is beyond the goals of the present article, they are important to mention in the context of understanding and addressing the treatment gap.…”
Section: Critical Gaps In Treatmentmentioning
confidence: 99%
“…Previous studies identified several significant predictors of treatment seeking among individuals with EDs (see Ali et al, , for a comprehensive review), including high‐ED symptom severity, medical complications, and body image concerns (Cachelin, Rebeck, Veisel, & Striegel‐Moore, ; Cachelin & Striegel‐Moore, ; Forrest et al, ; Hepworth & Paxton, ; Mond et al, ; Schoen et al, ). These findings are likely due to the fact that greater symptom severity, concomitant physical health problems, and body dissatisfaction increase an individual's psychological distress and social/occupational role impairment.…”
Section: Introductionmentioning
confidence: 99%